A novel biomimetic hydrodynamic wake tracking principle inspired by harbour seal (Phoca Vitulina) vibrissae - Hans, Hendrik (2015)
The current study focuses on the underwater navigation inspired by harbour seals (Phoca Vitulina) vibrissae. Biological studies have illustrated the underwater sensing and tracking ability of harbour seals. These studies have exhibited the ability of the seals' vibrissae to track minute water velocities (up to 243 $μ m/s$) including tests in pools with background (water)noises. This depicts the robustness of the underwater sensing principle of the harbour seals' vibrissae. The evaluation of the underwater sensing principle of the seal vibrissae is performed through experiments and numerical simulations. The experiments are conducted in CENSAM water tank for measurements of forces on the vibrissa and its setups. Numerical simulations are utilised to provide insights into the physics of the flow around the structures. From these studies, it is found that the geometry of the vibrissavibrissae reduces Vortex-Induced Forces (VIF) and Vortex-Induced Vibration (VIV). Studies on the geometrical features of the vibrissa revealed that the existence of dual-axial undulations significantly reduces VIF and VIV while its drag coefficient is found to be similar to elliptical cylinder. For freely vibrating in crossflow and freely vibrating in streamwise and crossflow simulations, halved dominant crossflow response frequency is observed for the vibrissa as compared to that of circular and elliptical cylinders. From analysis of the wake, significant deformations of the vortex tubes and crossing of vortical braids from one plane to another (parallel to streamwise direction) are observed. These resulted in lower dominant response frequency of the vibrissa. It is also found that the spatial delay in vortex shedding dominates the desynchronization in the spanwise vortex shedding in reducing the amplitude of VIV. Experiments and simulations are also performed for sensory structure (i.e. vibrissa, elliptical cylinder and circular cylinder) trailing an equivalent diameter circular cylinder. For zero relative velocity between the generator and the sensor, it is found that the vibrissa and elliptical cylinder responded with significantly larger amplitude of oscillation and similar frequency of oscillation to the vortex shedding frequency of the generator. However, for non-zero relative velocity cases, the amplitude of oscillation is found to significantly decrease due to reduction in the duration of exposure of the sensory structure to the vortex tubes (perturbations). For approaching sensory structures, limiting approach speed is found to exist due to the greater modification of the vortices in the wake of the target at higher approach velocity (due to higher pressure build-up in the leading edge of the structure).